Hypotensive receptor mechanisms of Thymoquinone-treated ormotensive rats - Azzubaidi, Marwan Saad; Mizher, Hussam A.; Noor, Noriah Mohd (2014)
Introduction: Nigella sativa seeds “black cumin” have been widely used in traditional medicine for diseases treatment including hypertension. Thymoquinone (TQ) is one of the major active constituents in its volatile oil. Objectives: The objective of the current study was to confirm the blood pressure lowering effect of TQ, and to investigate its mechanism through muscarinic and β adrenergic receptors. Methods: Mean arterial blood pressure (MAP) was recorded using the non-invasive blood pressure tail cuff technique. Dose-response relationship was obtained after using 3 TQ doses (2.5, 5 and 10 mg/kg) intraperitoneally to 3 different groups (n=5) of adult male Sprague Dawley rats under pentobarbital anesthesia. MAP was then measured for other 2 animal groups pretreated either with atropine (P-at) or propranolol (P-pro) followed by 10mg/kg TQ. Results: TQ produced a dose-dependent blood pressure lowering effect, where 2.5 mg/kg reduced MAP by 8±1 mmHg, whereas 5 and 10 mg/kg of TQ treatment decreased MAP by 12±3 and 29±3 mmHg, respectively. TQ-induced MAP reduction was significantly less in P-at than non-pretreated group. Conversely, TQ-induced MAP reduction in P-pro did not demonstrate significant difference from the non-pretreated group. Conclusion: This study confirms the dose-related hypotensive effect of TQ and provides an evidence for the traditional use of Nigella sativa for treatment of hypertension. The mechanism of TQ-induced hypotension involves at least in part activation of vascular muscarinic receptors, but not β-adrenergic receptors.